Formal and Informal Learning Experiences in Second Life: An Overview - William C. Diehl (Adult Education Research Conference, 2008)
A growing number of higher education institutions, consortiums and libraries are establishing presences in the virtual world of Second Life. Millions of adults currently engage in both formal and informal learning experiences in SL and the numbers are growing. This paper provides an overview of this phenomenon.
Keywords: Second Life; virtual reality; communities of practice; informal learning